DNA barcodes and morphology reveal new species within the Rheotanytarsus guineensis species group from China (Diptera: Chironomidae) - Li, Shu‐Yi; Yao, Yuan; Sun, Li; Ling, Hai‐Ning; Jin, Wei‐Dong; Lin, Xiao‐Long (Archives of insect biochemistry and physiology, 2023)
The Rheotanytarsus guineensis species group (Diptera: Chironomidae) is a species diverse and taxonomically difficult group. Using DNA barcodes, we found five new species within the R . guineensis species group and reviewed the species group based on adult males from China. Rheotanytarsus guoae Lin & Yao sp. n ., Rheotanytarsus miaoae Lin & Yao sp. n ., Rheotanytarsus qiangi Lin & Yao sp. n ., Rheotanytarsus yueqingensis Lin & Yao sp. n ., and Rheotanytarsus yui Lin & Yao sp. n . are all described and figured. A key to known adult males of the R . guineensis species group worldwide is provided for the first time. We have reviewed the Rheotanytarsus guineensis species group from China and detected five new species using DNA barcodes. These five new species are described and figured based on adult males. A key to known adult males of the R . guineensis species group worldwide is provided for the first time.